Design and Analysis of High Survivable Heterogeneous Emergency Communication Network - Haitao Wang; Xueping Zhang; Hui Chen (Dianxin kexue)
According to characteristics and requirements of emergency communication,high survivable heterogeneous emergency communication network based on wireless self-organized network was constructed to provide a reliable and flexible communication support platform for emergency site.Firstly,traits and survivable demands of heterogeneous emergency communication network were explained.Secondly,the design of high survivable heterogeneous emergency communication network was expounded and analyzed in detail,including networking mode,design strategy and network structure.Finally,some countermeasures which could improve survivability of emergency communication network further were discussed.